Adsorption and micellisation of partially- and fully-fluorinated surfactants - Downer, A; Eastoe, J; Pitt, A; Penfold, J; Heenan, R (1999)
Effects of chemical structure on adsorption and aggregation behaviour have been investigated for sodium perfluorononanoate (C8F17COO- Na+ or Na PFN) and 9-H perfluorononanoate (H-C8F16COO- Na+ or H Na PFN). Replacing the terminal F for H in this way gives rise to a permanent dipole moment at the hydrophobic tip of the chain. The critical micelle concentrations, determined by surface tension and electrical conductivity, were 10 and 40 mmol dm-3 for the Na PFN and H Na PFN, respectively. Tensiometric and neutron reflection (NR) methods were employed to investigate adsorption at the air-water interface. Problems associated with the experimental measurements, and data interpretation, are discussed. In particular effects on surface tensions of trace levels of Ca2+, Mg2+ and Ba2+, as well as the sequestering agent ethylenediaminetetraacetic acid (EDTA), were investigated. The background levels of a principal contaminant, Ca2+, were directly measured by atomic absorption spectrophotometry, indicating a typical ratio of Ca2+:Na+ of 1:104 in these surfactant solutions. Hence, an appropriate level of added EDTA, sufficient to chelate unwanted polyvalent metals but enough not affect the surface tension, was chosen and this was EDTA:surfactant 1:333. For both compounds the surface excess Γ obtained from NR data was consistently higher than that derived from tensiometry, using a Gibbs pre-factor of 2. However, better agreement was found if this was changed to 1.7, which would be consistent with around 30% dissociation of counterions from the film. At the critical micelle concentration (cmc) the fully fluorinated surfactant adsorbs most strongly, in that NR gave areas per molecule for the Na PFN and H Na PFN of 41 and 44 A2, respectively, whereas drop volume tensiometry gave 43 and 51 A2. Taking together all the different methods, at their cmc's the average values were 43.1±3.4 and 48.4±5.2 A2 for the Na PFN and H Na PFN, respectively. These changes are consistent with weaker intermolecular interactions in the layer, and stronger adsorption, in the absence of the H-CF2 dipole. Aggregation in the bulk was also investigated by small-angle neutron scattering (SANS), and the data were modelled in terms of charged spherical micelles. At a volume fraction φ(mic)~0.05, the micellar radii and net charges were similar, being 15 and 14 A, -10 and -13, for Na PFN and H Na PFN, respectively. These values suggest that the ion dissociation in micelles is between 25 and 45%, and this is similar to the ionisation at the surface suggested by the adsorption measurements. These results will help improve understanding about properties of fully- and partially-fluorinated surfactants, which are often used in speciality applications, such as water-in-CO2 microemulsions. Copyright (C) 1999 Elsevier Science B.V.